Late Quaternary stratigraphy, sedimentology and geochemistry of an underfilled lake basin in the Puna plateau (northwest Argentina). (3rd July 2013) - McGlue, Michael M.; Cohen, Andrew S.; Ellis, Geoffrey S.; Kowler, Andrew L.
Abstract Depositional models of ancient lakes in thin‐skinned retroarc foreland basins rarely benefit from appropriate Quaternary analogues. To address this, we present new stratigraphic, sedimentological and geochemical analyses of four radiocarbon‐dated sediment cores from the Pozuelos Basin (PB; northwest Argentina) that capture the evolution of this low‐accommodation Puna basin over the past ca. 43 cal kyr. Strata from the PB are interpreted as accumulations of a highly variable, underfilled lake system represented by lake‐plain/littoral, profundal, palustrine, saline lake and playa facies associations. The vertical stacking of facies is asymmetric, with transgressive and thin organic‐rich highstand deposits underlying thicker, organic‐poor regressive deposits. The major controls on depositional architecture and basin palaeogeography are tectonics and climate. Accommodation space was derived from piggyback basin‐forming flexural subsidence and Miocene‐Quaternary normal faulting associated with incorporation of the basin into the Andean hinterland. Sediment and water supply was modulated by variability in the South American summer monsoon, and perennial lake deposits correlate in time with several well‐known late Pleistocene wet periods on the Altiplano/Puna plateau. Our results shed new light on lake expansion–contraction dynamics in the PB in particular and provide a deeper understanding of Puna basin lakes in general.